Implementasi Case Method Pada Pengembangan Modul Digital Simulasi Jaringan Komputer untuk Mendukung Kecakapan Abad 21 Mahasiswa - Nashiroh, Putri Khoirin; Ristanto, Riska Dami; Ekarini, Fitria; Widianingtyas, Wahyu Yulia; Khoerunnisa, Ana; Hasanah, Nadzifatul (Peneliti.net, 2024)
Informatics and Computer Engineering Education (ICEE) students as prospective vocational high school teachers have a big challenge in teaching hard skills and educating future skills of vocational high school students. Therefore, ICEE students need to be accustomed to learning in conditions that support their 21st-century skills. This study aims to develop and test the validity of the computer network simulation digital module by implementing the case method to support students' 21st-century skills. Learning media in digital modules designed with the case method is expected to support ICEE students' 21st-century skills while overcoming problems often experienced by students in computer network practice. The method used is research and development (R&D), which stages of analysis, design, development, and testing. The digital module was tested on media experts and material experts. The module also tested 32 ICEE students to analyze perceptions of their 21st-century skills. Media Expert Testing gave a result of 95.5%, and material experts gave a result of 97%, which showed that digital modules have a very valid category. The trial results gave an average percentage score of Student perceptions for Communication Skills of 86%, Collaboration Skills of 88%, Critical Thinking and Problem-Solving Skills of 84.25%, and Creativity and Innovation Skills of 84%, which showed a very high category. Thus, based on ICEE student perceptions, this computer network simulation digital module can be used to train students' 21st-century skills.